2017
DOI: 10.1016/j.maturitas.2017.02.003
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of outcome measures to assess postural control in older adults who undertake exergaming

Abstract: Gillian (2017) A systematic review and meta-analysis of outcome measures to assess postural control in older adults who undertake exergaming. Maturitas, Published by: Elsevier

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 52 publications
1
18
0
2
Order By: Relevance
“…Results of the initial search strategy, evidence level and quality assessment please refer to [16]. Results of the additional search strategy, evidence level and quality assessment can be found in supplementary file 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Results of the initial search strategy, evidence level and quality assessment please refer to [16]. Results of the additional search strategy, evidence level and quality assessment can be found in supplementary file 1.…”
Section: Resultsmentioning
confidence: 99%
“…The reporting of this systematic review was performed according to the PRISMA guidelines [25]. Full details of the inclusion and exclusion criteria and the search strategy are provided in an earlier paper reporting interventions effects according to primary, secondary and tertiary PC outcomes in exergaming interventions [16]. Succinctly, randomized control trials (RCTs) and non-randomized control trials (non-RCTs) that assessed and reported PC outcomes were included.…”
Section: Study Selection Criteria Search Strategy and Quality Assessmentioning
confidence: 99%
See 1 more Smart Citation
“…Ce type de programme serait également efficace pour améliorer la mobilité des seniors (Schwenk et al, 2014). Ces entraînements ont principalement ciblé les améliorations du contrôle postural des seniors avec succès (Tahmosybayat, Baker, Godfrey, Caplan, & Barry, 2017). Ils présenteraient donc un intérêt particulièrement important dans la réduction du risque de chute de ces publics sachant que l'entraînement de l'équilibre est reconnu comme le meilleur moyen d'éviter les chutes (Sherrington et al, 2008).…”
Section: Entraînement à Domicile Avec Semi-supervisionunclassified
“…Ils présenteraient donc un intérêt particulièrement important dans la réduction du risque de chute de ces publics sachant que l'entraînement de l'équilibre est reconnu comme le meilleur moyen d'éviter les chutes (Sherrington et al, 2008). Cependant, les résultats sont moins importants qu'avec d'autres techniques d'améliorations de l'équilibre comme des entraînements de fitness en groupe, ou du Tai Chi (Tahmosybayat et al, 2017). Les améliorations d'équilibre observées seraient également plus faibles après les entraînements à domicile que lors d'entraînement en groupe dans les centres d'entraînement (Cyarto, Brown, Marshall, & Trost, 2008).…”
Section: Entraînement à Domicile Avec Semi-supervisionunclassified